Role of Service Innovation in Enhancing Loyalty to Online Travel Agencies - Rasmidatta, Vatanyoo (KKBS Journal of Business Administration and Accountancy, 2022)
This study aimed to answer the following questions. (1) Is the latest proposed measurement model for customer engagement suitable for online travel agencies (OTAs) in Thailand? (2) Is the proposed conceptual model suitable for the travel agent business in Thailand? If yes, how much can the predictive power of service innovation trigger customer engagement and collectively predict brand loyalty? (3) Does current customers’ awareness of service innovation trigger service evaluation and customer engagement? In this quantitative empirical research, the researcher employed a questionnaire as an instrument for collecting data. The researcher collected data from 478 respondents by using online and off-line surveys. The findings are as follows: (1) service innovation influences customer engagement, (2) perceived value influences customer engagement, (3) customer engagement influences brand loyalty, (4) perceived value influences brand loyalty, and (5) service innovation influences brand loyalty. This study provides two major contributions. First, the integration of customer engagement, service innovation, and service evaluation was explored in the context of Thailand hotels promoted by OTAs, widening the existing nomological network. Second, this study calculated the predictive power of brand loyalty drivers, and thus, practitioners could reap the benefits from the suggestions on how to predict and promote brand loyalty conditional to the level of service innovation and customer engagement.